Comparison of the Effectiveness of Acceptance and Commitment-Based Parenting and Schema-Based Parenting on Competence and Self-Control in Children with Oppositional Defiant Disorder - Khaghani, Fatemeh; Golparvar, Mohsen; Yousefi, Zahra (KMAN Counseling & Psychology Nexus, 2025)
This study was conducted with the aim of comparing the effectiveness of acceptance and commitment-based parenting and schema-based parenting on competence and self-control in children with oppositional defiant disorder. The research employed a quasi-experimental design with three phases: pretest, posttest, and follow-up, along with a control group. The statistical population consisted of all mothers and their children who visited three child counseling and psychotherapy centers in Isfahan during Autumn 2024, from whom 60 mother–child pairs were selected through convenience sampling and assigned to two experimental groups and one control group (20 participants per group). The Competence Questionnaire (Merrell et al., 2011) and the Self-Control Questionnaire (Humphrey, 1982) were used to measure the dependent variables across the three phases. The acceptance and commitment-based parenting group and the schema-based parenting group each received training separately across nine sessions of 75 to 95 minutes, while the control group received no training. Data were analyzed using repeated-measures ANOVA and Bonferroni post-hoc tests via SPSS version 26. The results showed a significant difference in competence and self-control between the acceptance and commitment-based parenting group and the schema-based parenting group compared to the control group (p < .05). When comparing the two parenting approaches, no significant difference was found in competence (p > .05); however, regarding self-control, acceptance and commitment-based parenting demonstrated greater effectiveness than schema-based parenting (p < .05). Based on the findings, acceptance and commitment-based parenting and schema-based parenting can be used to enhance competence and self-control in children with oppositional defiant disorder.